Look behind you [compact disc, unabridged] : a novel - Johansen, Iris; Johansen, Roy (Johansen, Iris. Kendra Michaels series., 2017)
Cooperating with the FBI when a serial killer begins leaving relics at his crime scenes, Kendra Michaels discovers that the objects are souvenirs from other unsolved murders and that the new killings have been orchestrated to taunt her.